Challenges and Opportunities for Nurse Managers Working in Nepal's Level II and III COVID Hospitals - Pudashini, Pramila; Sigdel, Rambha; Shah, Tara; Khatiwada, Sarita; Yadav, Manju (Journal of Karnali Academy of Health Sciences, 2022)
Introduction: Following the COVID-19 outbreak, nurse managers encountered many challenges in carrying out theirmanagement duties. There were difficulties with determination and decision-making but there is yet opportunity forimprovement. However, there were few studies done in this field; as a result, researchers selected this subject to find out thelevel of management Awareness (AWE) Challenges (CHA), and Opportunities (OPA) faced by nurse managers as a result ofCOVID-19, followed by an analysis of the relationship of socio-demographic characteristics such as age, marital status,experiences, and training on awareness (AWE) of the COVID-19 pandemic management.Methods: Researchers utilized a cross-sectional method and a quantitative approach in this investigation. Purposive samplingapproaches were used along with self-administered questionnaires to get the data. Ninety-three nurse managers from differentgovernment hospitals in Nepal participated in this study. The validity and reliability of the instrument were examined. Bothdescriptive statistics and inferential statistics, such as regression analysis, were employed.Results: The finding revealed that; a maximum number of nurse managers have an average level of COVID-19 pandemicmanagement awareness (39%), challenges faced after the COVID-19 pandemic (36%), and opportunities related to the COVID-19 pandemic (35%), respectively. However, years of work experience and training have shown a positive relationship toenhance awareness.Conclusion: The nurse managers experienced challenges and had average levels of awareness. However, they also noticed achance in the learning opportunity. This lesson will teach managers to be ready for upcoming emergencies. Therefore, a studyhas shown that experienced managers and training could be useful to improve leadership in the healthcare sector.